ADDRESSING CHALLENGES AND EXPLORING OPPORTUNITIES FOR INNOVATIVE TECHNOLOGIES IN ASTROPHYSICS EDUCATION - Diyor Rashidov (PEDAGOGS, 2024)
Abstract: Adopting advanced technologies like virtual reality (VR), augmented reality (AR), and interactive simulations in astrophysics education offers exciting possibilities for improving student engagement and comprehension. However, educators and institutions face various obstacles, such as limited resources, complex subject matter, and a lack of tailored training. This study examines the current barriers to implementing innovative technologies in astrophysics instruction and discusses actionable approaches to overcome these hurdles. Through understanding these challenges, educators can better leverage technology to create dynamic learning experiences in this complex scientific field.